Answered

Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Is the expression -12x-18 equivalent to the expression -6x-9-3(3-2x)

Sagot :

-12x-18 and -6x-9-3(3-2x)

First, distribute the -3 into the parentheses. The second expression will turn out as such:
-6x-9-9-6x.
From here, you need to combine like terms (variables and numbers). -12x-18.
So, yes, these two expressions are equal.
-12x-18=-6x-9-3(3-2x)
-12x-18=-6x-9-9+6x
-12x-18=-6x+6x-9-9
-12x-18=-18
-12x-18=-18
+18=+18
-12x=0
X=0
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.